LANGUAGE MANAGEMENT IN FAMILY PLANNING DISCOURSES AT MACHAKOS LEVEL 5 HOSPITAL, KENYA - MAITHA, JULIANA N. (My University, 2019)
In Kenya and particularly Machakos County, there is low prevalence of family planning uptake which stands at 49.7%. Family Planning (FP) is not only a health issue but also a cultural and linguistic concern. Therefore, lack of attention to culture and linguistic aspects in communication can negatively impact on the quality of FP services offered and thus contraceptive uptake. The study sought to analyse the language problems in family planning discourses at Machakos Level 5 Hospital. The study was motivated by previous studies in other countries that show that existence of language barriers affect uptake of family planning services. The study employed qualitative research design. The study was guided by Neustupny and Jernudd (1987) Language Management Theory (LMT) and supplemented with Grice (1975) Cooperative Principle and Leech (1983) Politeness Theory. The study was guided by four research objectives: to identify service related language problems at Machakos level 5 Family Planning Department; to analyse how language problems are evaluated; to assess adjustment strategies to the language problems; and to analyse mechanisms for the implementation of the adjustment strategies. The study randomly sampled 20 service seekers and purposively included 15 service providers. The researcher observed 13 service seeker – service provider interactions that were recorded. An interview schedule guide was used to administer interviews to all the 15 service providers and 15 service seeker that were recorded which were later transcribed. Document analysis checklist was used to analyse written family planning materials. The recorded data was transcribed and analysed. The study findings show that Cooperative Principle and Politeness Theory maxims are violated and the deviations are evaluated negatively leading to language problems. This study demonstrated that language problems led to six undesirable consequences: miscommunication; dissatisfaction with services; poor service delivery; hindering access to family planning services; increased sense of vulnerability; and failure to seek consent. Further, the study established that there are various adjustment design strategies that are designed to mitigate the language problems. At simple management level, these strategies include; avoidance, pre-interaction management, code switching among others while at organized management level, there are written materials in place. The study noted that there are mechanisms of implementing the adjustment designs selected. For example, at the micro level, participants became rude, others came along with their relatives for interpretation services and providers made use of their colleagues while at the macro level; the written materials such as charts were seen pinned on notice boards and clients were issued with leaflets and brochures. The study concluded that Machakos Level 5 Hospital does not provide adequate language services despite existence of language problems. Further, the study concludes that service providers lack cultural and linguistic competency to offer culturally sensitive healthcare and recommends the facility to offer language services. Based on these findings, the study recommends: training of medical staff to equip them with interpersonal communication skills that take care of linguistic and cultural diversity; Machakos Level 5 Hospital to provide professional interpretation and translation services; and Machakos Level 5 Hospital to translate family planning materials into Kikamba and Swahili.